WALK OR SWIM: THE SUBSTRATE FOR MOVEMENT AFFECTS MATE CHOICE BEHAVIORS IN FEMALES GRAY TREEFROGS (Hyla versicolor) - (:unkn) unknown (My University, 2024)
Semiaquatic animals breed in environments with a mix of aquatic and terrestrial features, each requiring appropriate types of locomotion with differential energetic demands and containing different suits of predators. We surveyed calling locations of male Eastern Gray Treefrogs (Hyla versicolor) at our study pond to assess average composition of land/water substrates available to females during mate choice. We also conducted acoustic playback trials to examine whether the mate choice behavior of females was affected by approach substrate; i.e., whether females had to swim or walk towards a potential mate. We found that mate preferences were not strongly affected by the substrate of movement: peak preference for longer duration calls was similar in both treatments, but females showed somewhat higher preference selectivity in the water treatment. By contrast, other aspects of phonotaxis behavior were clearly different and consistent with females perceiving water as a more dangerous environment: in the water treatment, females took longer to leave the dry release point, jumped further when leaving the release point, and took advantage of features of the playback setup (i.e., the aquatic arena was surrounded by walls) to leave the water and approach the speaker “on land”. This suggests that females do not compromise mate preferences but adjust associated behaviors to minimize risk, and that environmental heterogeneity does not alter sexual selection regimes.
Keywords: call duration; Hyla versicolor; mate preference; preference selectivity